Strategi Manajemen Pembelajaran Paud Dalam Mengembangkan Potensi Anak Usia Dini (Studi Kasus Di Lembaga Pendidikan Anak Usia Dini An Nisa Tegaldlimo Banyuwangi) - Dewi Lyien Ien; Mirhabun Nadzir; M. Bisri Ikhwan (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to determine early childhood learning management strategies in developing the potential of early childhood at the An Nisa Tegaldlimo Banyuwangi early childhood education institution. This research uses qualitative research with a case study approach. The data analysis was carried out circularly, starting from the overall data display from the results of interviews, observations and documentation obtained while in the field. The results obtained show that PAUD learning activities consist of Teaching and Learning Activities, Review of the Educational Calendar, and Arrangement of Learning Schedules. Guidelines for learning organizations relate to defining stages of development, capacity indicators, defining knowledge concepts introduced, determining themes, developing learning activities, preparing tools and materials. Learning planning strategies must pay attention to SKH (Daily Activity Units) and SKM (Weekly Activity Units). The curriculum must be structured based on By paying attention to the differences that exist in society, students can recognize the diversity of social life. Learning class settings are held in accordance with the school's vision and mission. Teachers' teaching activities start from welcoming students at the front of the school gate, carrying out lessons, escorting students to the front gate until the children are picked up by their respective parents. Early childhood learning activities include learning while dancing or moving; Drawing/coloring while learning; and memorize words while clapping.